PENGARUH KETEBALAN MATERIAL TANAH DAN KEMIRINGAN LERENG TERHADAP POTENSI LONGSOR PADA SETIAP SATUAN BENTUKLAHAN DI SUB DAS KODIL, JAWA TENGAH - , ZUHARA RIZQYAN C ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kodil watershed is a part of Bogowonto watershed. The location of Kodil Watershed is in the frontier of Purworejo, Magelang and Wonosobo Regency. This area located on the foot slope of Sumbing Volcano which has unique morphology. Morphology of Kodil watershed formed by exogenic processes, such as weathering, erosion and mass movement. Denudation process that worked at the bed rock that formed by structural control and volcanic activity, causing topography formed by steep slope and thick soil material. This conditions influence the landslide potential. This research using stratified aligned sampling method (transect) for slope and soil thickness measurement. Census method is used to collecting the point and distribution of landslides. Data analysis in this research using descriptive analysis method by made the transect lineâs profile and simple tabulation. The result of this research show that landslide potential influenced by slope and soil material thickness. Landslide potential is high at the middle of catchment area. This area usually has a steep slope, between 20% - 65%, and the soil material is formed by colluviums, about 5 meters.